Penerapan Konsep Bela Negara, Nasionalisme Atau Militerisasi Warga Negara - Sri Indriyani Umra (Universitas Islam Indonesia, 2019)
State Defense is the determination, attitude and behavior of citizens imbued with their love for the Unitary State of the Republic of Indonesia which is based on Pancasila and the 1945 Constitution, willing to sacrifice to ensure the survival of the State. The formulation of the problems in this study is the following: First, what is the concept of State Defense in Indonesia? Second, what are the advantages and disadvantages of the enforcement of State Defense in Indonesia today? The method in this study is normative using primary legal materials, secondary legal materials and tertiary legal materials. The approaches used in this research are the legislation approach, conceptual approach and case approach. After analysing, it is known that the concept of State Defense which focuses more on the understanding of noble values in Pancasila in relation to character or behavior and the author sees this study in two different perspectives as outlined in the form of policy on the enforcement of State Defense by relying on legislation through policies about State Defense. It is not appropriate for a state defense program to be carried out suddenly by the Ministry of Defense, as it should be the domain of the Ministry of Education hence we provide solutions that can be realized in several programs including: Intra-curricular by integrating the education program of State Defense awareness and building national character into various eyes lesson; as well as extra-curricular by implementing intra-culicular activities into various extra-curricular activities that can be applied in community life with the implementation planned carefully and integrated with the education curriculum so that the young generation is observed and evaluated. In essence, the application of the training program must be adjusted to the guidance of the current era in the implementation of State Defense in Indonesia.